Performance of soft limiters in the LMS algorithm for cyclostationary white Gaussian inputs - Bershad, Neil J.; Eweda, Eweda; Bermudez, Jose C.M. (Signal processing, 2018)
The analysis of saturation-type nonlinearities on the input and the error in the weight update equation for LMS adaptation were obtained for a stationary white Gaussian data model in [28] for system identification. Here the input signal is modeled by a cyclostationary white Gaussian random process with periodically time-varying power. The system parameters vary according to a random-walk. Using the previous analysis results, nonlinear recursions are presented for the transient and steady-state weight first and second moments that include the effect of the soft limiters. Monte Carlo simulations of the algorithms provide strong support for the theory.